Open ankle dislocation without associated malleolar fracture: Review of the literature. (April 2017) - Elsayed, Hassan; Thalava, Ramesh; Afifi, Hytham; Khan, Mohammad
Abstract: Open ankle dislocation without an associated fracture is an extremely rare injury [1]. We present a case of a 17-years old male who sustained a serious injury of his right ankle during jumping downstairs. He twisted his ankle and sustained an open posteromedial dislocation of his right ankle, without an associated malleolar fracture. The treatment consisted of wound debridement and irrigation open relocation with repair of anterior talo-fibular ligament, and primary closure of the skin post operatively the limb was immobilised in short leg cast for six weeks in a neutral position allowing partial weight bearing. At the 3-month follow-up visit, the patient reported that both ankle and feet had regained full, pain-free range of motion and he returned to full activity.